Yours, Mine and Ours? Sharing and Use of Technology in Domestic Environments - Brush, A.J.; Inkpen, Kori (Ubicomp 2007, 2007)
Domestic technologies have been a popular area of study for ubiquitous computing researchers, however there is relatively little recent data on how families currently use and share technologies in domestic environments. This paper presents results from an empirical study of 15 families in the U.S in early 2007. We examined the types of technologies families own, including TVs, music players, phones and computers; where they were situated within the home; and the degree of shared ownership and use. Our results call attention to the prevalence of shared usage of technology in domestic environments and also suggest opportunistic spaces for ubiquitous computing technology. While not all ubiquitous computing technologies for domestic environments will be shared, the diverse ways families chose to share their computers suggest that future devices might better match how families wish to use shared technology by supporting both the shared usage model of appliances and the ability to access a personal profile.